Analysis of Determinants of Open Unemployment in North Sumatra - E, Efri Ramadhana; Hasyim, Sirojuzilam; Syafii, M. (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the factors influencing open unemployment in North Sumatra Province from 2012 to 2024. It investigates the effects of macroeconomic variables, including economic growth, inflation, provincial minimum wage (UMP), investment, and population growth, on open unemployment, with the moderating role of the Human Development Index (IPM). The research employs a quantitative approach using panel data analysis, encompassing data from 33 districts/cities in North Sumatra. The findings suggest that economic growth, inflation, and provincial minimum wage significantly affect open unemployment, while investment and population growth play a less significant role. Furthermore, the moderating effect of IPM is crucial in enhancing or reducing the impacts of these variables. The study provides valuable insights for policymakers and the private sector in formulating strategies to reduce unemployment and improve human capital development in the region.